The influence of service delivery failures, service recovery and perceived values on customer behavioural intentions in Malay restaurants / Zulhan Othman - Othman, Zulhan (Institute of Graduate Studies, UiTM, 2015)
Undeniable in restaurant operation service delivery failures occurred when service delivery performance does not meet the expectations of customers and classified as either pertaining to the outcome or process. A process failure happened when core service carried in a flawed or incomplete way, resulting in poor benefit and instigating in reduction of economic resources such as money, time, status or esteem to the customer. Knowing failures will occur even in the finest restaurant, it is imperative therefore for the restaurant to make provisions for recovery of these unfavourable instances and the provisions that restaurant makes are known as service recovery. Restaurant ability to recover from service delivery failure is an essential element of the whole service delivery system with significant implications as it is recognized to provide opportunities to decrease costs, improve customer experience and increase customer satisfaction. The effective service recovery not only corrects the service delivery failures, but also builds and maintains strong relationships which ultimately lead to behavioural intentions, including revisiting and word of mouth. In contrary, as to why customers are found of still patronizing some of the restaurants despite providing fewer recovery processes. It is therefore conjectured that the role of positive perceived values may influence customers repeat purchase behaviour or the underlying reasons that cause this causation. This study empirically investigates the causal relationship among service delivery failures, service recovery and perceived values with satisfaction and behavioural intentions of customers towards Malay medium restaurants…